Analisis Media Monitoring: Sentimen Publik Terhadap Inovasi Produk Brand Indomie Pada Periode Maret 2024 - Nabila Zahra (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
. Indomie as the market leader of instant noodles in Indonesia often launches flavor innovations with culinary flavors typical of certain regions. During 2024, Indomie has released three flavor innovations, namely the authentic Japanese Indomie Tori Kara in collaboration with the Pop Mie brand, Indomie Goreng Rawon Pedas Mercon from East Java, and Indomie Goreng Kebuli flavor from the Middle East. Thus, it is necessary to conduct media monitoring to monitor the development of netizens' responses to the Indomie product innovation. This research uses a positivism research paradigm with a quantitative descriptive research method that optimizes the use of Brand24 tools to obtain sentiment data, mentions and reach, and trending hashtags from online media. The results of Indomie's media monitoring research in the March 2024 period show that the number of positive Indomie sentiments tends to increase every week with the X application and Tiktok as the largest source of sentiment. This increase was influenced by several factors such as influencers, the use of hashtags, and the momentum of Ramadan 2024. In addition, Indomie also received negative sentiments from netizens regarding the quality of flavors that differ in each region and the comparison of Indomie with its competitors which are considered superior.